Viscosity and viscometric fixed points of glass Part 1. Recommendations for use in the determination of viscosity and viscometric fixed points (BSI, 1988)
Glass, Viscosity, Viscosity measurement, Liquids, Temperature measurement, Error analysis, Calibration, Test specimens, Softening point, Working range, Annealing, Phase transformations, Softening-point determination, Melting, Control samples, Samples, Temperature, Reference point determination, Strain, Test equipment, Specimen preparation, Equations, Critical temperature